Micro-start-ups financial capital and socio-economic performance: In a poor financial resource setting - Khan, Eijaz Ahmed Khan; Quaddus, Mohammed; Weber, Paull; Geneste, Louis (2020)
The micro-start-ups financial capital dimensions and its relationships are unique because it operates a business in a poor financial resource setting. However, micro-start-ups poor financial resource settings are not adequately explored into the literature. Therefore, drawing upon the resource-based view (RBV), the current paper attempts to examine the dimensions of financial capital with respect to a measurement model, and to test the direct and indirect relationships between financial capital dimensions and performance. Using a mixed method research design, at first, in the qualitative part, we obtained data from 14 cases via one-to-one personal interview: eight micro-start-ups, three NGOs, and three Local governments. Content analysis was applied to extract, classify, and cross examine of the data. In the quantitative part, a questionnaire was developed, and data were collected from 438 micro-start-ups. We analyzed the data by using the partial least square structural equation modeling (PLS-SEM). Results are well vibrated with the existing literature and establish a model and the hypothesis. The study used a field study data to produce new items and confirm existing items recognized by RBV in the literature review. This process also assessed the content validity of the items. After confirming the content validity, this study formally specifies the measurement model. The measurement model confirmed a valid scale for measuring sources of finance, capital structure and socio-economic performance in the context of micro-start-ups. The findings of this study showed that there is significant statistical evidence to support a positive relationship between sources of finance and capital structure, capital structure and socio-economic performance, and sources of finance and socio-economic performance. The study also observed that that capital structure plays a partial indirect effect in explaining the relationship between sources of finance and socio-economic performance. Policy makers and relevant agencies may design specific strategies to alleviate micro-start-ups financial resource difficulties. They may revisit the existing micro-credit programmes and evaluate the risk tolerance of small capital. They should develop a special package of capital structure for micro-start-ups. It might also be interesting to shed some additional light on the sources of finance, for example, specifically address whether financing from NGOs plays a vital role.